2003
DOI: 10.3109/bctg.44.6.347.355
|View full text |Cite
|
Sign up to set email alerts
|

Primary MALT-Lymphoma of the Liver: Multimodality Imaging

Abstract: MALT lymphoma rarely affects the liver. We present a case of primary MALT lymphoma of the liver, which appeared as multifocal hyperattenuated lesions compared to the fatty liver on unenhanced CT and as moderately hyperintense on T2-weighted and hypointense on T1-weighted MRI. We describe the radiological imaging features and discuss the differential diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…[22,24] Meanwhile, distinctive radiological features were absent. Ultrasound studies showed majority of the hepatic MALT lymphomas as hypoechoic masses, [7,15,16,22,26,29,31,40,43] which was in agreement with a previous study of liver lymphomas. [51] On contrast-enhanced CT, primary hepatic MALT lymphoma had been described as low-density mass, which was not enhanced, [16,17,31,39] or faint enhanced, [15,36,40] or enhanced peripherally in the early arterial phase.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[22,24] Meanwhile, distinctive radiological features were absent. Ultrasound studies showed majority of the hepatic MALT lymphomas as hypoechoic masses, [7,15,16,22,26,29,31,40,43] which was in agreement with a previous study of liver lymphomas. [51] On contrast-enhanced CT, primary hepatic MALT lymphoma had been described as low-density mass, which was not enhanced, [16,17,31,39] or faint enhanced, [15,36,40] or enhanced peripherally in the early arterial phase.…”
Section: Discussionsupporting
confidence: 91%
“…Ultrasound studies showed majority of the hepatic MALT lymphomas as hypoechoic masses, [7,15,16,22,26,29,31,40,43] which was in agreement with a previous study of liver lymphomas. [51] On contrast-enhanced CT, primary hepatic MALT lymphoma had been described as low-density mass, which was not enhanced, [16,17,31,39] or faint enhanced, [15,36,40] or enhanced peripherally in the early arterial phase. [29] MRI was characterized by low signal intensity on T1-weighted images and moderately high signal intensity on T2-weighted images, and the enhancement pattern was similar to that of CT. [15,22,35,36,40,43] Our case also had these radiological features.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3,8 Literature MRI findings of primary hepatic MALT lymphoma are similar to those in our case, including hypointensity on T1-weighted images, moderate hyperintensity on T2-weighted images, and a slight and peripheral enhancement pattern. 9 Therefore, in most cases, the preoperative diagnosis was non-specific, prompting biopsy (8,9) or surgery if there was suspicion of cholangiocellular carcinoma 3,7 or hepatocellular carcinoma. 8 The etiology of hepatic primary lymphoma is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…There are no positive serum markers, and imaging studies such as MRI, computed tomography, and US do not yield patterns with features specific to hepatic MALT lymphoma (17).…”
Section: Review Of the Literature And Discussionmentioning
confidence: 99%